Peran Tour Leader Dalam Manajemen Krisis Akomodasi Hotel Pada Penyelenggaraan Umrah - Muna Ahda Sabila; Kurnia Muhajarah (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
The implementation of modern Umrah pilgrimage services faces various administrative and operational challenges that may lead to accommodation crises for pilgrims. The implementation of the Nusuk platform and the mandatory possession of Tasreh documents require a more structured managerial preparedness from Umrah travel organizers to mitigate accommodation-related risks. This study aims to analyze the strategic role of Tour Leaders at Nida’ul Khoirot Tour & Travel in planning hotel availability and managing crises in the field using a qualitative case study approach. Data were collected through in-depth interviews with five key informants representing management, Tour Leaders, and pilgrims. The findings reveal two main results. First, the risk of accommodation failure can be mitigated through a strict full-payment policy prior to visa issuance and multi-layered administrative verification within the Nusuk application. Procedural compliance plays a crucial role in securing pilgrims’ accommodation rights and protecting them from unauthorized intermediary practices. Second, in responding to operational crises such as delays in hotel check-in access, Tour Leaders demonstrated tactical responsiveness by arranging temporary transit accommodations supported by flexible financial autonomy. Service quality optimization was further strengthened by the emotional intelligence of Tour Leaders, manifested through psychological compensation in the form of culinary tours during transportation delays and mobility assistance initiatives for elderly pilgrims. In conclusion, the reliability of administrative risk mitigation and the application of empathetic leadership by Tour Leaders contribute significantly to maintaining operational comfort, service quality, and the spiritual focus of pilgrims during the Umrah journey.